Design and Development of a Multisensory Real-Time Monitoring Platform for Ultrafast Laser Engraving Process - Roozbahani Hamid; Alizadeh Marjan; Handroos Heikki; Salminen Antti (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2022)
Process online monitoring is a vital and integral part of high-speed laser scribing process in which speed and quality are paramount. In this study, a multi-sensory platform for real-time monitoring of the ultrafast pulsed laser engraving process has been developed. Four different sensors have been examined from various perspectives and the results have been analyzed and compared. The real-time monitoring system developed for this study consisted of IPG ytterbium pulsed fiber laser, scan head, illumination system, and four monitoring sensors, including a spectrometer, pyrometer, infrared (IR) camera, and high-speed camera. Various experiments were performed to evaluate the performance of the designed platform by applying each sensor to monitor a high-speed laser scribing process in real-time. The output of each sensor was analyzed by changing different laser and process parameters, such as laser power, focal position, beam speed, and pulse length. Strengths, weaknesses, and challenges of using each monitoring tool for the laser engraving process were discussed based on the obtained results.